Design and Implementation of The Tracer Study System at PTKI - Mayreyna Nurwardani; Mohammad Khoerul Anwar; Lindra Darnella; Annisa Mufti Allifa (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aims to (1) provide an academic basis for the Indonesian Ministry of Religion's DIKTIS and PTKI to formulate policies related to the importance of alumni trace research; (2) provide a manual for the implementation of tracer studies for PTKIN and PTKI so that the implementation of tracer studies is standardized; and (3) establishing a tracer studies system for PTKI, so that tracer studies can be carried out effectively, easily, efficiently and sustainably. Tracer study is useful for knowing the distribution and monitoring of potential alumni of a university, in this case PTKI and PTKIN. Methods of carrying out this research include; making the design of the tracer study system, testing the tracer study system, and disseminating the tracer studies system. The results of this study are the renewal of the tracer study system belonging to PTN.X and the availability of guidebooks related to the importance of tracer studies and implementation guidelines.Keywords: Design, PTKI, Tracer Study.